2006
DOI: 10.1111/j.1365-2958.2006.05445.x
|View full text |Cite
|
Sign up to set email alerts
|

Different roles of P1 and P2 Saccharomyces cerevisiae ribosomal stalk proteins revealed by cross‐linking

Abstract: The stalk is an essential domain of the large ribosomal subunit formed by a complex of a set of very acidic proteins bound to a core rRNA binding component. While in prokaryotes there is only one type acidic protein, L7/12, two protein families are found in eukaryotes, phosphoproteins P1 and P2, which presumably have different roles. To search for differences zero-length cross-linking by S-S bridge formation was applied using Saccharomyces cerevisiae mutant P1 and P2 proteins carrying single cysteine residues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…These results suggest that the A 1 chain of SLT-1 binds to the C terminus of P1 and/or P2 but most likely to P2 due to its exposure in the cytosol while binding to another location on RPP0 in close proximity. [27][28][29] Our studies show that type II RIPs, the SLT-1 A 1 chain as well as the A chain of the plant toxin RTA, also recognize the conserved C terminus 17 amino acids of ribosomal stalk proteins (Fig. 5a).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…These results suggest that the A 1 chain of SLT-1 binds to the C terminus of P1 and/or P2 but most likely to P2 due to its exposure in the cytosol while binding to another location on RPP0 in close proximity. [27][28][29] Our studies show that type II RIPs, the SLT-1 A 1 chain as well as the A chain of the plant toxin RTA, also recognize the conserved C terminus 17 amino acids of ribosomal stalk proteins (Fig. 5a).…”
Section: Discussionmentioning
confidence: 91%
“…19,20,[24][25][26] The P2 C terminus is left exposed. [27][28][29] RPP0 has been shown to bind to rRNA via its N-terminal region (Fig. 5b).…”
Section: Discussionmentioning
confidence: 97%
“…The function of the other ribosomal stalk P-proteins, which share the same conserved CTD, is not clear. Despite the high sequence similarity between P1/P2 proteins, their biophysical and functional properties are different [25,36]. Previous cross-linking experiments showed differences in the reactivity of P1 and P2 and suggested that the P1 protein, which displayed restricted reactivity, is internally located, whereas the P2 protein is more external and accessible to interact with the other cellular components [36].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the high sequence similarity between P1/P2 proteins, their biophysical and functional properties are different [25,36]. Previous cross-linking experiments showed differences in the reactivity of P1 and P2 and suggested that the P1 protein, which displayed restricted reactivity, is internally located, whereas the P2 protein is more external and accessible to interact with the other cellular components [36]. Moreover, fluorescence correlation spectroscopy experiments suggested that the function of P1–P2 dimers is not equally distributed [36,37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation